2011
DOI: 10.5897/ajmr11.502
|View full text |Cite
|
Sign up to set email alerts
|

Detection of inducible clindamycin resistance by an automated system in a tertiary care hospital

Abstract: Clindamycin is commonly used in treatment of erythromycin resistant Staphylococcus aureus causing skin and soft tissue infections. In vitro routine tests for clindamycin susceptibility may fail to detect inducible clindamycin resistance due to 'erm' genes resulting in treatment failure thus necessitating the need to detect such resistance by a rapid method. In the era of automation, vitek-2 system provides a panel for detection of inducible clindamycin resistance with conjunction of other antimicrobial suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…Of these, 3% (9/300) isolates were constitutively resistant while 33% (99/300) were inducibly resistant (D-test positive). Similar studies have been conducted including one in India that reported a prevalence rate of 54% S. aureus resistance to CL of which 12% constitutively resistant and 43% Inducibly resistant [ 16 ]. Still in India Shantala et al 2011 reported prevalence rate of 43.15% S. aureus resistance to CL with 18.26% (42/230) constitutively resistant and 24.89 % (57/230) inducibly resistant [ 17 ].…”
Section: Discussionmentioning
confidence: 53%
“…Of these, 3% (9/300) isolates were constitutively resistant while 33% (99/300) were inducibly resistant (D-test positive). Similar studies have been conducted including one in India that reported a prevalence rate of 54% S. aureus resistance to CL of which 12% constitutively resistant and 43% Inducibly resistant [ 16 ]. Still in India Shantala et al 2011 reported prevalence rate of 43.15% S. aureus resistance to CL with 18.26% (42/230) constitutively resistant and 24.89 % (57/230) inducibly resistant [ 17 ].…”
Section: Discussionmentioning
confidence: 53%
“…To avoid treatment failure, it is therefore necessary to detect such resistance by, for instance, a simple D ‐test on a routine basis (Jethwani et al . ; Prabhu et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…1,[28][29][30][31] The lowest prevalence was reported 3.5% by Kalpana D, Mamta C, Vilas T at Nagpur district and highest resistance was reported 90% by Dizbay M, Gunal O, Ozkan Y et al 32,33 However Deshmukh et al, reported 14.8% inducible clindamycin resistance. 19,[34][35][36] In this study, Overall prevalence of constitutive resistant isolates was 28%, Gurdal Yilmaz 17,18,29,31 Angel MR, Balaji V, Prakash J et al, didn't report any constitutive resistance in their study and Saderi H, Emadi B and Owlia P reported about 93% constitutive clindamycin resistance in their study. 34,37 In the present study, Chloramphenicol (74%) showed higher sensitivity pattern followed by Clindamycin (72%), where resistant isolates were higher in Penicillin-G (80%…”
Section: Resultsmentioning
confidence: 99%